Diseases Neglected by the Media in Espírito Santo, Brazil in 2011-2012. - Aline Guio Cavaca; Tatiana Breder Emerich; Paulo Roberto Vasconcellos-Silva; Edson Theodoro dos Santos-Neto; Adauto Emmerich Oliveira (Public Library of Science (PLoS), 2016)
The aims of the present study were to identify and analyse the Diseases Neglected by the Media (DNMs) via a comparison between the most important health issues to the population of Espírito Santo, Brazil, from the epidemiological perspective (health value) and their effective coverage by the print media, and to analyse the DNMs considering the perspective of key journalists involved in the dissemination of health topics in the state media.Morbidity and mortality data were collected from official documents and from Health Information Systems. In parallel, the diseases reported in the two major newspapers of Espírito Santo in 2011-2012 were identified from 10,771 news articles. Concomitantly, eight interviews were conducted with reporters from the two newspapers to understand the journalists' reasons for the coverage or neglect of certain health/disease topics.Quantitatively, the DNMs identified diseases associated with poverty, including tuberculosis, leprosy, schistosomiasis, leishmaniasis, and trachoma. Apart from these, diseases with outbreaks in the period evaluated, including whooping cough and meningitis, some cancers, respiratory diseases, ischaemic heart disease, and stroke, were also seldom addressed by the media. In contrast, dengue fever, acquired immune deficiency syndrome (AIDS), diabetes, breast cancer, prostate cancer, tracheal cancer, and bronchial and lung cancers were broadly covered in the period analysed, corroborating the tradition of media disclosure of these diseases. Qualitatively, the DNMs included rare diseases, such as amyotrophic lateral sclerosis (ALS), leishmaniasis, Down syndrome, and verminoses. The reasons for the neglect of these topics by the media included the political and economic interests of the newspapers, their editorial line, and the organizational routine of the newsrooms.Media visibility acts as a strategy for legitimising priorities and contextualizing various realities. Therefore, we propose that the health problems identified should enter the public agenda and begin to be recognized as legitimate demands.